The burden and treatment of non-communicable diseases among healthcare workers in sub-Saharan Africa: a multi-country cross-sectional study - Müller, Sophie Alice; Elimian, Kelly; Rafamatanantsoa, Jean Florent; Reichert, Felix; Mosala, Francis; Böff, Lena; Touré, Sounan Fidèle; Boone, Idesbald; Ravaoarisoa, Lantonirina; Nduenga, Sagesse; Ortu, Giuseppina; Pozo-Martin, Francisco; et al. (Frontiers in Public Health, 2024)
Introduction Non-communicable diseases (NCDs), the leading cause of death globally, are estimated to overtake communicable diseases in sub-Sahara Africa, where healthcare workers (HCWs) play a crucial role in prevention and treatment, but are in extreme shortage, thereby increasing the burden of NCDs among this specific population. To provide evidence for policy-making, we assessed the NCD burden, associated factors and treatment among HCWs in four sub-Saharan African countries. Materials and methods We conducted a cross-sectional study across four sub-Saharan African countries [Côte d'Ivoire (CIV), Democratic Republic of the Congo (DRC), Madagascar (MDG), and Nigeria (NIG)] between February and December 2022. In a standardized questionnaire, sociodemographic, chronic disease and treatment data were self-reported. We estimated the prevalence of (1) at least one chronic disease, (2) hypertension, and used backward elimination logistic regression model to identify risk factors. Results We recruited a total of 6,848 HCWs. The prevalence of at least one chronic disease ranged between 9.7% in NIG and 20.6% in MDG, the prevalence of hypertension between 5.4% in CIV and 11.3% in MDG. At most, reported treatment rates reached 36.5%. The odds of each of both outcomes increased with age (at least one chronic disease adjusted odds ratio: CIV: 1.04; DRC: 1.09; MDG: 1.06; NIG: 1.10; hypertension: CIV: 1.10; DRC: 1.31; MDG: 1.11; NIG: 1.11) and with BMI (at least one chronic disease: CIV: 1.10; DRC: 1.07; MDG: 1.06; NIG: 1.08; hypertension: CIV: 1.10; DRC: 1.66; MDG: 1.13; NIG: 1.07). Odds of both outcomes were lower among males, except in CIV. In NIG, the odds of both outcomes were higher among medical doctors and odds of hypertension were higher among those working in secondary care. In MDG, working in secondary care increased and working as auxiliary staff decreased the odds of at least one chronic disease. Conclusion The prevalence of self-reported chronic disease varied across the four sub-Saharan countries with potentially very low treatment rates. We identified several individual (age, sex, and BMI) and occupational (profession, level of healthcare) factors that influence the odds of NCDs. These factors should be taken into account when developing interventions addressing the burden and management of NCDs among HCWs.